Protarcys Klapálek, 1912, the senior synonym of Neofilchneria Zwick, 1973 (Plecoptera: Perlodidae) - Mo, Raorao; Li, Weihai; Murányi, Dávid (Zootaxa, 2025)
Study of the type specimens of both nominal species included in the poorly known Perlodinae genus Protarcys Klapálek, 1912 proved them congeneric with the four known species of Neofilchneria Zwick, 1973. Consequently, Protarcys is the senior synonym of Neofilchneria, and belongs to Arcynopterygini instead of Perlodini. Four new combinations are stated: Protarcys cheni (Zhang, Li & Li, 2024), P. erberi (Zwick, 1980) (in: Zwick & Sivec 1980), P. uncata (Kimmins, 1947), P. wanglanga (Chen, 2019). The two original species, P. caudata Klapálek, 1912 and P. lutescens Klapálek, 1912 are redescribed on the basis of type specimens. The genus is known from China (Hubei, Sichuan, Xizang and Yunnan), India (Sikkim) and Nepal. Keys are presented for distinguishing the species of Protarcys.